Prevalence of the palmaris longus and its impact on grip strength in elite gymnasts and non-athletes - Eric, M.; Yammine, K.; Vasic, G.; Dejanovic, M.; Karaba, D. (International Journal of Morphology, 2019)
In elite athletes, the palmaris longus (PL) presence has a potential contribution to hand strength, smallerreaction time, better shooting speed and power. The aim of this study was to investigate the prevalence of PL in elitecompetitive artistic gymnasts and its impact on grip strength compared to a control group of moderately active non-athletes.This prospective study included 370 subjects divided in two groups (170 elite artistic gymnasts and 200 moderately activenon-athletes, students of medicine). The study consisted of two clinical sets of examination: a search for the clinical presenceof PL was initially conducted followed by the assessment of maximal grip strength. Standard and six additional tests wereperformed to confirm PL tendon absence. Maximal grip strength was measured bilaterally with an electronic handdynamometer. Bilateral absence was more common than unilateral, predominately noted on left side in both study groups.Unilateral PL absence was correlated to decreased grip strength in students, while the opposite was found in gymnasts. Themean value of grip strength in some age groups was higher on the side where the PL was absent. The results of our studyshow that the presence of the PL doesn`t affect the hand grip strength in gymnasts. Due to the low incidence of unilateral PLabsence, further large-sampled research is warranted to assess PL contribution to hand grip strength and to other handfunctions that could be of significant importance for athletes and non-athletes.